The Oxford handbook of economics and human biology - Komlos, John, 1944-; Kelly, Inas Rashad (New York : Oxford University Press, 2016)
The Oxford Handbook of Economics and Human Biology provides an extensive and insightful overview of how economic conditions affect human well-being and how human health influences economic outcomes. The book addresses both macro and micro factors, as well as their interaction, providing new understanding of complex relationships and developments in economic history and economic dynamics. Among the topics explored is how variation in height, whether over time, among different socioeconomic groups, or in different locations, is an important indicator of changes in economic growth and economic development, levels of economic inequality, and economic opportunities for individuals. The book covers a broad geographic range: Africa, Latin and North America, Asia, and Europe. Its temporal scope ranges from the late Iron Age to the present.
East Asia on the Rise / Daniel Jong Schwekendiek -- Introduction / Inas R. Kelly, John Komlos -- Racial Differences in Health in the United States / Leah Boustan, Robert A. Margo -- Inequality and heights / Matthias Blum.
Also issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human biology -- Economic aspects; Industry; Industry & industrial studies